2009
DOI: 10.1159/000220260
|View full text |Cite
|
Sign up to set email alerts
|

Renin and Prorenin Activate Pathways Implicated in Organ Damage in Human Mesangial Cells Independent of Angiotensin II Production

Abstract: Background: The mechanism by which an activated renin-angiotensin system (RAS) leads to the development of renal diseases, such as fibrosis, is only partially explained by the downstream effects of angiotensin II. The discovery of a receptor that binds renin and prorenin, and the consequent production of profibrotic molecules, revealed a novel axis within the RAS pathway that may contribute to the pathogenesis of organ damage in patients with elevated renin and/or prorenin levels. Methods: To better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Among them, we suggest that the acute changes of systemic hemodynamics in ADHF patients might influence PRA before changing entire RAAS activation. Furthermore, recent experimental studies have raised the possibility that the (pro-) renin receptor plays pathological roles in the progression of HF [30,31]. Recent studies also suggest that there are multiple and complex pathways regulating RAAS activation, which are related to cortisol [32], parathyroid hormone [33] and inflammation [34].…”
Section: Renin-angiotensin-aldosterone System Factors In Adhf Patientsmentioning
confidence: 99%
“…Among them, we suggest that the acute changes of systemic hemodynamics in ADHF patients might influence PRA before changing entire RAAS activation. Furthermore, recent experimental studies have raised the possibility that the (pro-) renin receptor plays pathological roles in the progression of HF [30,31]. Recent studies also suggest that there are multiple and complex pathways regulating RAAS activation, which are related to cortisol [32], parathyroid hormone [33] and inflammation [34].…”
Section: Renin-angiotensin-aldosterone System Factors In Adhf Patientsmentioning
confidence: 99%
“…It was shown that both have a similar transcriptional signature that is independent of Ang production. Importantly, the changes in gene expression induced by renin and pro-renin were consistent with the development of organ damage and fibrosis, primarily through TGF-b mechanisms [32].…”
Section: Pulmonary Fibrosis E Montes Et Almentioning
confidence: 74%
“…Melnyk et al [83], by performing a gene expression profiling study in human mesangial cells, found that 20 nmol/l renin and 50 nmol/l prorenin (in the presence of 10 mmol/l M6P to block M6P/IGFII receptors) activated pathways implicated in organ damage. Among others, COX-2 up-regulation was observed.…”
Section: Kidney and Diabetesmentioning
confidence: 99%